Survival Strategy and the Role of Technology in Measures of E-Business Progress in E-Commerce Applications - Wahyu Andriansyah Naibaho; Niki Aulia; Nurbaiti Nurbaiti (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
This study aims to find out how the strategy is to survive for the sake of the progress of the Ebusiness business with the progress of the virtual world at this time, the Internet has experienced an up (growth), decline (decline) and growth again. Not many companies that are involved in E-Business are able to adapt to the life cycle experienced by the internet. The benefits of e-business are not only from speeding up and practicing the company's internal processes, but also from its ability to spread profits to other members of the supply chain. Organizations can also add positive value to consumers through products and services in many ways that e-business can. Moreover, in a rapidly changing environment, the implementation of e-business can allow organizations to create competitive advantages to win the competition. Electronic Commerce (e-commerce) is the process of buying, selling or exchanging products, services and information via computer networks. ecommerce is part of the e-business, where the scope of e-business more broadly, not just commercial but also include business partners, customer service, job vacancies.